Negociación y el manejo de riesgos - Grindsted, Anette (HERMES - Journal of Language and Communication in Business, 2008)
The article defends the position that it is the construction of interpersonal relations that determines the zone of possible agreements in a negotiation rather than ‘economic’ considerations. It is assumed that negotiation is a communicative activity that implies risk and that to be able to initiate negotiations it is a precondition that a certain degree of trust has been established between the parties. Two different ways of conceptualizing trust are described, and two e-mail negotiations that give empirical support to these conceptualizations are analyzed. One reaches a dead-lock, the other does not.